Elucidation of improving effects of a traditional Japanese herbal formula, hochuekkito, comprising Atractylodis rhizoma, on T‐cell‐mediated intestinal mucositis in mice. Issue 2 (15th July 2022) - Endo, Mari; Utagawa, Shiori; Nagai, Takayuki; Hanawa, Toshihiko; Odaguchi, Hiroshi; Kiyohara, Hiroaki
Abstract: Aim: Hochuekkito has been used for gastrointestinal immune depression. Among its 10 herbal components, Atractylodis rhizoma (AtR) and Atractylodis lanceae rhizoma (ALR), and also Hedysari radix (HR) and Astragali radix (AR), can be interchanged based on the patient's symptoms. However, the difference between these formulas for improving gastrointestinal immune depression is not clear. The aim of this study was to compare the effect of AtR‐ and ALR‐ hochuekkkito on a T‐cell‐mediated systemic and small intestinal mucosal inflammation model. We also analyzed the active ingredients and mechanism of action of AtR‐ hochuekkito on the antiapoptotic effect in the Fas/FasL‐mediated signaling cascade on intestinal epithelial cells. Methods: The effects of hochuekkito, lipophilic ingredients, and oligosaccharides on the systemic and small intestinal mucosal inflammation induced by anti‐CD3 antibody were analyzed. The effect of the AtR formula on mRNA expression of molecules related to the apoptotic signaling cascade was analyzed. Results: AtR‐ hochuekkito improved intestinal mucosal inflammation even if HR and AR were interchanged. Meanwhile, only the ALR formula suppressed systemic inflammation, whereas the AtR formula failed to improve it even if HR was replaced with AR. AtR formula administration increased gene mRNA expression of antiapoptotic regulatory adapter molecules in the small intestine of anti‐CD3 administered mice. The lipophilic ingredients in the AtR formula improved the effect on the small intestinal mucosal inflammation; liquiritin was an active ingredient. The intermediate‐size inulo‐oligosaccharides suppressed the recruitment of cytotoxic CD8 lymphocytes in the small intestine. Conclusion: AtR‐ hochuekkito is suitable for the treatment of small intestinal mucosal inflammation induced by spontaneous activation of T lymphocytes.